The Model Of Based Business Performance Improvement Model Co-Creation Value (Study Of Hijab Fashion Msmes In West Java) - Yuliati Yuliati; Agus Rahayu; Eeng Ahman; Heni Hendrayati (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to develop a model for improving business performance through the co-creation of value in hijab fashion MSMEs in West Java. Co-creation, which involves active collaboration between businesses and customers, has been recognized as a key factor in driving innovation and competitive advantage. By examining the role of co-creation in the context of micro, small, and medium enterprises (MSMEs), particularly within the hijab fashion industry, this research seeks to identify the main drivers that enhance business performance. Data were collected through surveys and interviews with hijab fashion MSME owners and customers in West Java. Using statistical analysis, the study found that co-creation activities such as customer engagement, collaborative design, and shared experiences significantly contribute to improved customer satisfaction, product innovation, and overall business performance. The findings suggest that implementing co-creation strategies can help hijab fashion MSMEs achieve sustainable growth and maintain a competitive edge in the fashion market. This research contributes to the growing body of literature on co-creation value and MSME business performance improvement.